The Usefulness of Patient-Reported Outcomes and the Influence on Palliative Oncology Patients and Health Services: A Qualitative Study of the Prospective Outcomes and Support Initiative. Issue 5 (September 2021) - Howard, A. Fuchsia; Medhurst, Kerensa; Manhas, Domnick S.; Yang, Linda Y.; Brown, Steven; Brown, Erika; Olson, Robert A.
Abstract : Background: Through the British Columbia, Prospective Outcomes and Support Initiative (POSI), registered nurses collect patient-reported outcome (PRO) data during telephone follow-up with palliative oncology patients. Objective: The research objective was to describe the usefulness and influence of the nursing care provided through POSI follow-up on palliative patients and health services. Methods: We used a qualitative interpretive description approach involving the collection and analysis of semistructured interview data with 20 palliative patients and 12 oncology nurses. All participant data were subjected to an inductively derived coding framework. Analytic categories were identified and iteratively revised through constant comparative techniques to develop representative themes. Results: The accounts of patients and nurses suggest that telephone follow-up with PROs enabled the nurses to (1) focus on the priorities of patients experiencing complex health challenges, (2) manage complex symptoms, (3) ease the patient's transition home, and (4) improve access to and use of health services. Suggestions for improving POSI nurse follow-up centered on flexibility in the timing of the follow-up, creating dedicated POSI work assignments, and having additional time to personalize assessments and nursing care beyond the PRO questionnaires. Conclusions: Nursing care employing PROs via telephone follow-up can improve palliative cancer patients' quality of life and health service use. Implications for Practice: Nurses are optimally positioned to use PROs following cancer treatment completion but require organizational resources and support to optimize patient and system outcomes.